(19b-6)-9(2b+4)=-2

Simple and best practice solution for (19b-6)-9(2b+4)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (19b-6)-9(2b+4)=-2 equation:


Simplifying
(19b + -6) + -9(2b + 4) = -2

Reorder the terms:
(-6 + 19b) + -9(2b + 4) = -2

Remove parenthesis around (-6 + 19b)
-6 + 19b + -9(2b + 4) = -2

Reorder the terms:
-6 + 19b + -9(4 + 2b) = -2
-6 + 19b + (4 * -9 + 2b * -9) = -2
-6 + 19b + (-36 + -18b) = -2

Reorder the terms:
-6 + -36 + 19b + -18b = -2

Combine like terms: -6 + -36 = -42
-42 + 19b + -18b = -2

Combine like terms: 19b + -18b = 1b
-42 + 1b = -2

Solving
-42 + 1b = -2

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '42' to each side of the equation.
-42 + 42 + 1b = -2 + 42

Combine like terms: -42 + 42 = 0
0 + 1b = -2 + 42
1b = -2 + 42

Combine like terms: -2 + 42 = 40
1b = 40

Divide each side by '1'.
b = 40

Simplifying
b = 40

See similar equations:

| 2(2)y+1=(2)y+3 | | 9x-8=16x+27 | | 12x+2.6=6.8x | | 54=3y+x | | 54=3x+y | | 2(x+9)=30+18 | | (19+3)2=x | | 5/4k=5 | | 54-3(45)= | | 5-2(4x-2)+2x= | | xa+5=7x+b | | -9(x+4)+2x+5=6x+11 | | Y=3*X+2 | | 3(45)+x+6(45)+4x=180 | | 4xy+5xy-3xz-2xy+xy+3xz= | | 8x+6-9x=2-y-15 | | 8-10p+4+8p= | | z(3+2i)=iz+2 | | 2(x+5)+5=2x+9 | | 3x-250=2858 | | 2x+15=385/(x+1) | | 3x+54-3x+6x+4(54-3x)= | | (x+3)(x^2+2x+6)=0 | | 1/16x-3/4y=-1 | | 5b-3/3b-4b+1/5b | | .2y+.5x=4.05 | | 2/3n=-18 | | -12=.5x+x | | 3y+x=54 | | 2(x+8)=30+18 | | 3x+y=54 | | 4x+4x=50 |

Equations solver categories